2021
DOI: 10.1007/s40262-020-00975-y
|View full text |Cite
|
Sign up to set email alerts
|

Limited Systemic Exposure with Topical Glycopyrronium Tosylate in Primary Axillary Hyperhidrosis

Abstract: Background Glycopyrronium tosylate (GT; Qbrexza ® [glycopyrronium] cloth, 2.4%) is a topical anticholinergic approved (USA) for primary axillary hyperhidrosis in patients aged ≥ 9 years. Objective The objective of this study was to compare the pharmacokinetics and safety of GT to oral glycopyrrolate (phase I study) and assess the relationship between glycopyrronium pharmacokinetics and anticholinergic-related adverse events or efficacy with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The authors reported increases in the mean plasma GP levels in the first 7-8 days of treatment, a small decline for the GPB 0Á5% and 1% cream during the next 7 days of treatment, and a more pronounced decline 7 days after the treatment period. 2 Interestingly, these values were spread out over a relatively large range. In the same phase Ib study, the maximum GP exposure, as measured by the peak concentration (C max ), were apparently below the respective values observed after oral administration, but the time to maximum plasma concentration (T max ) and the area under the curve (AUC) are not available.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The authors reported increases in the mean plasma GP levels in the first 7-8 days of treatment, a small decline for the GPB 0Á5% and 1% cream during the next 7 days of treatment, and a more pronounced decline 7 days after the treatment period. 2 Interestingly, these values were spread out over a relatively large range. In the same phase Ib study, the maximum GP exposure, as measured by the peak concentration (C max ), were apparently below the respective values observed after oral administration, but the time to maximum plasma concentration (T max ) and the area under the curve (AUC) are not available.…”
mentioning
confidence: 98%
“…In 2021, Pariser et al . reported the pharmacokinetic (PK) profile of GP tosylate wipes applied by patients with hyperhidrosis for 4 weeks with a 2‐week off‐drug follow‐up 4 . In view of the likely systemic absorption of topical anticholinergic agents, the possible risks of their long‐term use and the potential interindividual variability, especially in elderly patients, we believe that data on the PK profile of the GPB 1% cream formulation for a time period beyond 2 weeks are of great importance in real‐world practice and need to be considered and critically evaluated in an appropriately extended clinical trial programme.…”
mentioning
confidence: 99%
“…COVID-19 ARDS-prone individuals, such as those aged over 70 years, men and those with comorbid conditions, including obesity, diabetes or heart disease, will have reduced natural killer (NK) cell function compared with people without these characteristics. 2 A critical reduction in NK cell function would lead to immune dysregulation and thus aberrant response to a stimulus (SARS-CoV-2 infection in the case of COVID-19) and overproduction of cytokines, including interleukin (IL)-1b, IL-8, IL-17, tumour necrosis factor (TNF)-a and granulocytemacrophage colony-stimulating factor. Such cytokines would in turn promote neutrophil activation, with an increased neutrophil/lymphocyte ratio (NLR) and monocytosis.…”
mentioning
confidence: 99%
“…The PK data (C max ) of GP are predictive of anticholinergic adverse events (AEs) following topical application regarding frequency and severity. 2 As the frequency of systemic, anticholinergic AEs was lower after treatment with GPB cream than with GPT-containing wipes, 3,4 plasma concentrations after topical application of GPB cream are unlikely to exceed those of GPT-containing wipes.…”
mentioning
confidence: 99%
See 1 more Smart Citation